Rice Genotypes Express Compensatory Root Growth With Altered Root Distributions in Response to Root Cutting - Kawai, Tsubasa; Chen, Yinglong; Takahashi, Hirokazu; Inukai, Yoshiaki; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2022)
Root systems play a pivotal role in water and nutrient uptake from soil. Lateral root (LR) growth is promoted to compensate for inhibited main root growth. Compensatory LR growth contributes to maintaining total root length and hence, water and nutrient uptake in compacted soils. However, it remains unclear how shoot and root phenotypic traits change during the compensatory growth and whether there are genotypic variations in compensatory root growth. This study analyzed shoot and root morphological traits of 20 rice genotypes, including mutants with altered root morphology, during the vegetative stage using a semi-hydroponic phenotyping system. The phenotyping experiment detected large variation in root and shoot traits among the 20 genotypes. Morphological changes induced by root cutting were analyzed in six selected genotypes with contrasting root system architecture. Root cutting significantly affected root distribution along vertical sections and among diameter classes. After root cutting, more roots distributed at shallower depth and thicker LR development. Furthermore, genotypes with deeper root growth without root cutting allocated more compensatory roots to deeper sections even after root cutting than the genotypes with shallower rooting. Due to the compensatory LR growth, root cutting did not significantly affect total root length, root dry weight, or shoot dry weight. To analyze the interaction between crown root (CR) number and compensatory root growth, we removed half of the newly emerged CRs in two genotypes. Total root length of YRL38 increased at depth with CR number manipulation regardless of root tip excision, which was attributed to an increase in specific root length, despite no change in root dry weight. Taken together, the tested rice genotypes exhibited compensatory root growth by changing root distribution at depth and in diameter classes. Reducing CR number promoted root development and compensatory growth by improving the efficiency of root development (root length per resource investment).